An Environment of Environments: MAN transFORMS—Curatorial Modes, Designs, Structures. Issue 1 (2nd January 2019) - Korn, Samuel
Abstract: The article reflects on the conceptualization of the exhibition MAN transFORMS, the opening show of the Smithsonian Institution's National Museum of Design Cooper-Hewitt Museum in October 1976. Discussion of the exhibition's curatorial direction considers how conceptions of the environment are applied as content as well as form via reflection on the curatorial tools employed in the genesis of the exhibition's production between 1974 and 1976. MAN transFORMS was conceived by director Lisa Taylor together with architect Hans Hollein, and explored the potential of the newly-founded design museum in a series of commissioned environments and configurations of everyday objects, as well as collection exhibits. In the paper, I examine on the one hand the way the museum's institutional conditions rendered the environment a topic, and discuss, on the other hand, the terms within which the environment herein is used as a medium of architectural discourse.